Democracy - The Real 'Ghost' in the Machine of Global Health Policy; Comment on "A Ghost in the Machine? Politics in Global Health Policy" - Andrew Harmer (Kerman University of Medical Sciences, 2014)
Politics is not the ghost in the machine of global health policy. Conceptually, it makes little sense to argue otherwise, while history is replete with examples of individuals and movements engaging politically in global health policy. Were one looking for ghosts, a more likely candidate would be democracy, which is currently under attack by a new global health technocracy. Civil society movements offer an opportunity to breathe life into a vital, but dying, political component of global health policy.